Respuesta :
❥[tex]\Large\pmb{ \underline {\tt Answer}}[/tex]
#1
a + b • 3 = 3a + 3b
No
Actual equation formed:-
a + 3b = 3a + 3b
#2
- (a + 3b)3 = 3a + 9b
Yes
#3
a + b • 3 = a + 3b
Yes
#4
a + 3b • 3= 3a + 6b
No
Actual equation formed:-
a + 9b
#5
a + 3b • 3 = a + 9b
Yes
Rule applies:-
BODMAS
B - brakets
O - on/off
D- divide
M - multiply
A - add
S - subtract
━━━━━━━━━━━━━━━━━━
b. (a + 3b)3 = 3a + 9b
c. a + b • 3 = a + 3b
e. a + 3b • 3 = a + 9b
Hope that helps!
c. a + b • 3 = a + 3b
e. a + 3b • 3 = a + 9b
Hope that helps!